2014
DOI: 10.1007/s10096-014-2128-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the relationship between specific vaginal bacteria and bacterial vaginosis metronidazole therapy failure

Abstract: Bacterial vaginosis frequently persists, even after treatment. The role of some strains of bacteria associated with bacterial vaginosis treatment failure remains poorly defined. The aim of our study was to define the risk of bacterial vaginosis treatment failure, including pre-treatment detection of specific vaginal bacteria. Bacterial vaginosis is present when the Nugent score is ≥7 and the modified Amsel criteria is positive. Women with bacterial vaginosis were treated with intravaginal metronidazole gel nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 39 publications
1
20
2
Order By: Relevance
“…Other studies have shown that Veillonella spp. are associated with bacterial vaginosis, we believe that they could represent a risk factor for mesh contraction group . Moreover, we detected a trend of an association between higher bacterial diversity and mesh complications when compared with controls, although these findings were not statistically significant.…”
Section: Commentscontrasting
confidence: 51%
“…Other studies have shown that Veillonella spp. are associated with bacterial vaginosis, we believe that they could represent a risk factor for mesh contraction group . Moreover, we detected a trend of an association between higher bacterial diversity and mesh complications when compared with controls, although these findings were not statistically significant.…”
Section: Commentscontrasting
confidence: 51%
“…Oestrogen combined with E. coli is a widely used method to establish animal models of BV. Along with the high stability, these models can simulate the pathogenesis and clinical manifestation of BV (Wang et al , b). In the present study, this animal model was successfully established and confirmed by detecting the symptom indexes, CFU and neutrophil count, providing a solid guarantee for the subsequent experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, oral Metronidazole and Kanamycin vaginal suppository are widely used in the treatment of BV with a cure rate of about 80% (Klatt et al 2010). However, prior studies have found that adverse effects, such as vulvar swelling, prickling, nausea and headache, occurred during the treatment along with a high recurrence rate after the treatment (Wang et al 2014a. At present, the application of Lactobacillus capsule in the treatment of BV remains controversial, and its therapeutic effect is still inconclusive (Workowski and Bolan 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Intrauterine device use, a history of BV infection and the presence of bacterial species Facklamia, Corynebacterium and Veillonella are factors associated with BV treatment failure (Wang et al, 2014). Treatment of BV fails in up to 50% of cases (Schoeman, 2002;Hay, 2010).…”
mentioning
confidence: 99%
“…Treatment of BV fails in up to 50% of cases (Schoeman, 2002;Hay, 2010). Wang et al (2014) proposed that BV treatment failure is essentially due to the failed restoration of the lactobacilli population instead of antimicrobial resistance. It is suggested that for the effective treatment of BV, the restoration of Lactobacillus species to dominance alone will not suffice and that a decrease in BVassociated anaerobe concentrations below an unknown threshold is also required (Lambert et al, 2013a).…”
mentioning
confidence: 99%